Investigation of fungal bioaerosols in Shiraz composting facilities during 2017 - fariba fariba abbasi; Mohammad Reaz Samaei; hossein khodadadi; ali karimi; azadeh binaee haghighi; jamileh ekhlasi (Shiraz University of Medical Sciences, 2017)
Background: Fungi are one of the pollutant emissions from the composting plants which change in variety during the composting process. They are predominant in stabilization stage. Methods: This study assessed the thermotolerant airborne fungi based on NIOSH 0800 on 200 ambient samples from four composting processes and outdoor spaces in a composting plant. Results: The concentration of fungi during shredding, separatingand screening washigher than 1000 CFU/m3. The level of fungi in all stages was higher than outdoor(p<0.001). The highest concentration was detected in shredding (6749±1347 CFU/m3) (p=0.007), and the lowest concentration was related to screening (113±32 CFU/m3) (p=0.013). The predominant species was varied during the stages. Yeast andA.niger were predominant species in shredding and separating. Conclusion:The results of this study showed that the concentration of airborne fungi was decreased during composting process. The effect of these aerosols on indoor air was more than that in the outdoor space and workers at this sitewere exposed to high levels of thermotolerantfungi.Therefore,air-condition, ventilation system and safety operations such as respiratory masks are essential. The results of this studycan be used inrisk assessment.